2019
DOI: 10.1182/bloodadvances.2019032029
|View full text |Cite
|
Sign up to set email alerts
|

The stem cell–specific long noncoding RNA HOXA10-AS in the pathogenesis of KMT2A-rearranged leukemia

Abstract: Key Points• The lncRNA HOXA10-AS is highly expressed in KMT2A-rearranged AMLs and exerts its oncogenic effects by inducing NF-kB target genes.• Knockdown of HOXA10-AS reduces the leukemic growth of KMT2A-rearranged AML blasts in vivo.HOX genes are highly conserved, and their precisely controlled expression is crucial for normal hematopoiesis. Accordingly, deregulation of HOX genes can cause leukemia.However, despite of intensive research on the coding HOX genes, the role of the numerous long noncoding RNAs (ln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…In addition, our findings were supported by those of a previous study indicating that HOTAIRM1 expression was elevated in myeloid leukemia cells [ 18 , 21 ]. Additionally, other HOX cluster lncRNAs, such as HOXA10-AS and HOXB-AS3, have been reported to be significantly overexpressed in NPM1-mutated leukemia cells [ 39 , 41 ]. Deregulated lncRNAs have prognostic applications in AML [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our findings were supported by those of a previous study indicating that HOTAIRM1 expression was elevated in myeloid leukemia cells [ 18 , 21 ]. Additionally, other HOX cluster lncRNAs, such as HOXA10-AS and HOXB-AS3, have been reported to be significantly overexpressed in NPM1-mutated leukemia cells [ 39 , 41 ]. Deregulated lncRNAs have prognostic applications in AML [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, among the AR-interacting lncRNAs experimentally proved in this study, AL031714.1 and AC110285.1 expression correlated with tumor malignancy, and high AL031714.1 levels contributed to a bad prognosis. Moreover, HOXA10-AS was recently demonstrated to promote cell proliferation of lung adenocarcinoma [53] and KMT2A -rearranged leukemia [54] , although its expression was not found to correlate with either tumor grade or survival in prostate cancer. Thus, the interacting lncRNA partners of the prognostic signature constituent transcription factors may represent potential biomarkers and/or therapeutic targets in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Several lncRNAs are implicated in GC, such as HOTAIR [ 12 ], NEAT1 [ 13 ], and LINC01410 [ 14 ]. HOXA10 antisense RNA (HOXA10-AS) is a lncRNA and transcribed antisense to HOXA10 [ 15 ]. Intriguingly, HOXA10-AS is upregulated and functions as an oncogene in various cancers including leukemia [ 15 ], glioma [ 16 ], and oral cancer [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…HOXA10 antisense RNA (HOXA10-AS) is a lncRNA and transcribed antisense to HOXA10 [ 15 ]. Intriguingly, HOXA10-AS is upregulated and functions as an oncogene in various cancers including leukemia [ 15 ], glioma [ 16 ], and oral cancer [ 17 ]. Dong and colleagues reported that HOXA10-AS expression was elevated in glioma, and HOXA10-AS promoted glioma cell proliferation and enhanced apoptosis via activating HOXA10 expression [ 16 ].…”
Section: Introductionmentioning
confidence: 99%